THE ADVENTURE OF NAQY( NAHWU QURANY) NAHWU LEARNING SOLUTIONS BASED ON ONLINE GAMES - Pujirahayu, Nurjanah; Maulaya, Rosendah Dwi; Suryanita, Dev Nur; Avilya, Annisa (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Nahwu is the rules for knowing the form, state and position of the sentence when it is alone or composed . However, judging from the reality that there are many people who are lackingexplore and experience difficulties in studying the science of Nahwu and Shorof (Dodi, 2013 ) . Therefore, teaching media has an important role in learning foreign languages, especially in learning Arabic. Learning media is a means of delivering material that can help students understand, memorize, and digest subjects. The purpose of this research is to present a website -based design of Arabic teaching materials nahwu science learning packaged in interactive games with the Qur'an as an alternative to understanding Nahwu science. The research method used is research and development research and development) R&D research is carried out in stages including : analysis, design, development, implementation, and evaluation . The results of the study indicate that the creation of website -based Arabic teaching materials is needed because students are familiar with technology in the form of social media.